2016
DOI: 10.1021/acs.jpclett.6b00499
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Oxide/Metal Catalysts in Fundamental Studies and Practical Applications: A Perspective of Recent Developments

Abstract: Inverse oxide/metal catalysts have shown to be excellent systems for studying the role of the oxide and oxide-metal interface in catalytic reactions. These systems can have special structural and catalytic properties due to strong oxide-metal interactions difficult to attain when depositing a metal on a regular oxide support. Oxide phases that are not seen or are metastable in a bulk oxide can become stable in an oxide/metal system opening the possibility for new chemical properties. Using these systems, it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 81 publications
2
129
0
Order By: Relevance
“…For example, molecular hydrogen dissociation at a site spanning single palladium atoms on iron oxide (Fe 3 O 4 (001)) forms hydroxyls on the oxide via a heterolytic bond breaking process 23 . Migration of intermediates across interfaces between oxide islands of titania and ceria (TiO 2 and CeO 2 ) formed on gold and copper has also been demonstrated 64,65 . Similarly, copper oxidation was promoted by ceria (CeO 2 ) islands, indicating that oxygen transport across interfaces is also possible 66 .…”
Section: Discussionmentioning
confidence: 92%
“…For example, molecular hydrogen dissociation at a site spanning single palladium atoms on iron oxide (Fe 3 O 4 (001)) forms hydroxyls on the oxide via a heterolytic bond breaking process 23 . Migration of intermediates across interfaces between oxide islands of titania and ceria (TiO 2 and CeO 2 ) formed on gold and copper has also been demonstrated 64,65 . Similarly, copper oxidation was promoted by ceria (CeO 2 ) islands, indicating that oxygen transport across interfaces is also possible 66 .…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, researchers have increasingly recognized the importance of oxides in heterogeneous catalysis. Recently, it was found that the critical role of oxides in catalytic reactions became prominent when oxides covered metal surfaces forming inverse oxide/metal catalysts . This can be ascribed to the perturbations in the physical and chemical properties of the oxides originated from strong oxide−metal interactions, which is different from those of stable oxide phases in the traditional metal/oxide catalysts …”
Section: Figurementioning
confidence: 99%
“…Recently, it was found that the critical role of oxides in catalytic reactions became prominent when oxides covered metal surfaces forming inverse oxide/metal catalysts. [2][3][4] This can be ascribed to the perturbations in the physical and chemical properties of the oxides originated from strong oxide À metal interactions, which is different from those of stable oxide phases in the traditional metal/oxide catalysts. [5] In order to clarify the role of oxides in catalytic reactions, a series of inverse model catalysts, such as FeO x /Pt(111), [6] FeO x / Au(111), [6] CeO x /Cu(111), [7][8][9] CeO x /Au (111) and TiO x /Au(111), [10] FeO/Pt(111) and Cu 2 O/Ag(111), [11] have been prepared by the physical vapor deposition (PVD) method.…”
mentioning
confidence: 99%
“…This is due to the fact that the ZnO ultrathin film can spontaneously form on Cu nanoparticles disperse over ZnO particles in methanol synthesis by hydrogenation reactions of CO and CO 2 using commercial catalysts, Cu/ZnO/Al 2 O 3 . Sometimes, this is also referred to as “inverse catalyst”, with an oxide sitting on a metal, at variance with traditional catalysts . The ultrathin ZnO film on Cu not only prevents Cu from oxidation, but becomes an active phase speeding up the catalytic reactions .…”
Section: Introductionmentioning
confidence: 99%
“…[20,21,22] Sometimes, this is also referred to as "inverse catalyst", with an oxide sitting on a metal, at variance with traditional catalysts. [23,24] The ultrathin ZnO film on Cu not only prevents Cu from oxidation, but becomes an active phase speeding up the catalytic reactions. [21,22] The enhanced catalytic of metal supported ZnO films has been investigated to shed light on their properties, such as the ability to transfer charge from the underlying support to adsorbates [25] or the induced change in morphology of supported Au 20 clusters from tetrahedral structure (in gas phase) to planar 2D structure on the Cu (111) surface.…”
Section: Introductionmentioning
confidence: 99%